PERUBAHAN KANDUNGAN POLIFENOL DAN KEASAMAN BIJI KAKAO YANG DIFERMENTASI DENGAN PENAMBAHAN ENZIM KASAR POLIFENOL OKSIDASE DARI PULP KULIT BUAH KAKAO - La Teng, P Natsir; Yunus, Muh Ruslan; Kalsum, Kalsum (Jurnal Industri Hasil Perkebunan, 2016)
The aims of this research is to investigate changes in polyphenol contents and acidity of cocoabeans which were fermented by adding rough polyphenol oxidase enzymes, and dried by sun-dryingmethod. Enriched with nutrient, the rough enzymes was prepared from cocoa pod husk pulp. Fermentationtimes were varied at 16, 20, 24, 32, 36, 40, 44, and 48 hours, 2whereas the incubation periods of therough enzyme were varied at 24, 36, and 48 hours. Control treatment was also conducted by spontaneousfermentation for five days. Variables studied include polyphenol content, acidity, and reducing sugarcontent of the dried- cocoa beans. Results showed that fermentation by adding the rough polyphenoloxidase enzymes in the fermentation process could reduce polyphenol oxidation and acidification of thecocoa beans, compared to the spontaneous fermentation. This is indicated by the polyphenol contents(2.88-3.88 %), acidity (pH=5.25-6.50), and reducing sugar contents (0.60- 1.12%) of the dried cocoabeans in the fermentation by polyphenol oxidase enzyme addition for the six fermentation times, whilepolyphenol content, acidity (pH), and reducing sugar content of the dried beans were 0.98%, 52, and0.59%, respectively in the spontaneous fermentation.Keywords: cocoa beans, fermentation, polyphenol oksidase, polyphenol content, acidity. reducing sugarcontent